2013
DOI: 10.1167/iovs.12-11188
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Signaling in the Optic Nerve Is Necessary for Electrical Responsiveness of Retinal Ganglion Cells

Abstract: As experimental interventions were made at postretinal level(s), PERG changes were likely associated with altered supply of retrogradely-delivered material from the SC. This implies that retrograde transport of target-derived molecules is necessary for normal RGC electrical responsiveness. The time course of early PERG changes is consistent with the speed of fast retrograde axon transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 61 publications
(69 reference statements)
7
35
1
Order By: Relevance
“…6 The RGC counts showed massive (>85%) RGC loss in the operated eyes. Figure 3 of the study of Chou et al 6 shows that 1 month after ONC, the corneal PERG was dramatically reduced compared to the intact eye together with a major depletion of the RGC population, whereas Figure 4 of that study shows that the FERG was comparable in the two eyes. Figure 5 of the present study shows LED/snout PERGs derived from the right eyes of the 3 mice reported in the study of Chou et al 6 before and 1 month after ONC.…”
Section: Validitymentioning
confidence: 92%
See 2 more Smart Citations
“…6 The RGC counts showed massive (>85%) RGC loss in the operated eyes. Figure 3 of the study of Chou et al 6 shows that 1 month after ONC, the corneal PERG was dramatically reduced compared to the intact eye together with a major depletion of the RGC population, whereas Figure 4 of that study shows that the FERG was comparable in the two eyes. Figure 5 of the present study shows LED/snout PERGs derived from the right eyes of the 3 mice reported in the study of Chou et al 6 before and 1 month after ONC.…”
Section: Validitymentioning
confidence: 92%
“…As a control that the snout PERG reflected RGC activity as the corneal PERG, we used unpublished data on binocular snout PERG recorded in parallel with corneal PERG from a recent study of Chou et al 6 In that study, corneal PERGs and photopic FERGs were recorded in 3 C57BL/6J mice before and 1 month after unilateral, intraorbital optic nerve crush (ONC). 6 The RGC counts showed massive (>85%) RGC loss in the operated eyes.…”
Section: Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal ganglion cell function was assessed by means of the PERG, an electrical signal that specifically depends on RGC integrity [32][33][34] and is commonly used in human and experimental models of glaucoma and optic neuropathies. [35][36][37] Pattern electroretinograms were simultaneously recorded from both eyes according to a new paradigm recently described.…”
Section: Pattern Electroretinogrammentioning
confidence: 99%
“…Axonopathy at the junction between the retina and optic nerve is of particular interest, as it is believed to be the point of origin of glaucomatous neuropathy in humans 53 and mice. 35,54,55 As the PERG signal is also believed to be mainly generated by optic nerve axons in the optic nerve head, 33 axonopathy and astrocytic activation at this level may substantially impair the response.…”
Section: Tyr437his Mutant Of Human Myocilin Protein and Rgc Functionmentioning
confidence: 99%